The development of small island tourism in Malaysia - Fathilah Ismail (Victoria University, 2012)
In comparison to large islands and mainland destinations, economic development has often proven to be difficult for small island destinations due to common characteristics that include smallness in size, lack of resources (physical and human), isolated location, high transportation cost and limited capacity to earn export income.